Very high-power short-duration temperature-controlled ablation for cavotricuspid isthmus block : the Fast-and-Furious CTI study. (19th May 2022) - Kirstein, B; Vogler, J; Eitel, C; Phan, L; Feher, M; Keelani, A; Traub, A; D' Ambrosio, G; Grosse, N; Reincke, S; Hatahet, S; Trajanoski, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation for typical right atrial flutter (AFL) provides an effective treatment associated with encouraging clinical outcome. The novel micro-electrode ablation catheter allows very high-power short-duration (vHP-SD, 90 W/4 sec) ablation and potentially offers the ability to perform a safe, effective and faster cavotricuspid isthmus (CTI) ablation. Aims: We evaluated feasibility and efficacy of a vHP-SD (90 W/4 sec) temperature-controlled radiofrequency (RF) CTI ablation for AFL using a novel contact force (CF) sensing ablation catheter with micro-electrodes. Methods: Fifteen consecutive patients (median age 75 years (interquartile range, IQR: 67, 79), 67 % male) with documented typical AFL were prospectively enrolled and underwent vHP-SD based CTI ablation (90 W/4 sec). Durability of CTI block was proven by pacing maneuvers from both sides of the ablation line. Results: Complete CTI block using vHP-SD ablation was achieved in all patients (Figure 1). At median 23 (IQR 20; 39) RF applications over a median RF ablation time of 92 (IQR 78, 154) seconds were applied. It was not necessary to switch to the standard temperature-controlled mode to achieve durable CTI block. No periprocedural complications, no charring and no steam pops were observed. Conclusions: Very high-power short-duration (90 W/4 sec) CTI ablation for the treatment of typical AFL is feasible and efficient. Effective CTI block can be achieved in about 1.5 minutes of RF time.